2010
DOI: 10.1038/cr.2010.31
|View full text |Cite
|
Sign up to set email alerts
|

A de novo originated gene depresses budding yeast mating pathway and is repressed by the protein encoded by its antisense strand

Abstract: Recent transcription profiling studies have revealed an unexpectedly large proportion of antisense transcripts in eukaryotic genomes. These antisense genes seem to regulate gene expression by interacting with sense genes. Previous studies have focused on the non-coding antisense genes, but the possible regulatory role of the antisense protein is poorly understood. In this study, we found that a protein encoded by the antisense gene ADF1 acts as a transcription suppressor, regulating the expression of sense gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
116
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(119 citation statements)
references
References 34 publications
3
116
0
Order By: Relevance
“…This model has some features distinct from the current models for the origination of new nuclear genes [32,37,[40][41][42][43][44], including the "RNA-first" and "ORF-first" routes for generation of de novo genes [44]. Also notably, the CMS gene origination processes from the protogene orf367 to the functional genes WA352a/b/c and WA314 were completed within a relatively short timeframe in O. rufipogon (less than two million years [19]).…”
Section: Discussionmentioning
confidence: 99%
“…This model has some features distinct from the current models for the origination of new nuclear genes [32,37,[40][41][42][43][44], including the "RNA-first" and "ORF-first" routes for generation of de novo genes [44]. Also notably, the CMS gene origination processes from the protogene orf367 to the functional genes WA352a/b/c and WA314 were completed within a relatively short timeframe in O. rufipogon (less than two million years [19]).…”
Section: Discussionmentioning
confidence: 99%
“…When presented with environmental challenges, organisms adapt by using a range of strategies, including new enzymatic functions and novel regulatory processes. In natural systems, there are numerous precedents showing that selecting for growth under specified conditions can yield mutations that rewire gene regulation (27)(28)(29)(30)(31). For example, Taylor et al (27) showed that immotile mutants of Pseudomonas fluorescens subjected to selections for motility evolve by repurposing a protein that normally functions in nitrogen uptake toward a new function involving flagellar regulation.…”
Section: Discussionmentioning
confidence: 99%
“…A de novo originated gene has been described in yeast that acts to depress the mating pathway. Curiously, this gene in turn represses the protein encoded on its antisense strand (Li et al 2010b). A second example comes from Hydra in which the expression of a small, secreted orphan protein recapitulates phenotypic differences seen between species (Khalturin et al 2008).…”
Section: Evolution Of New Genesmentioning
confidence: 99%
“…Evolutionary divergence characteristics are commonly used as a filter to distinguish de novo gene candidates from neutrally evolving genomic regions. De novo gene emergence have been reported from many organisms such as insects (Begun et al 2007;Reinhardt et al 2013), yeast (Cai et al 2008;Li et al 2010b), Hydra (Khalturin et al 2008), primates (Johnson et al 2001;Knowles and McLysaght 2009;Toll-Riera et al 2009;Li et al 2010a;Wu et al 2011;Xie et al 2012), mouse (Murphy and McLysaght 2012;Neme and Tautz 2013), Plasmodium (Yang and Huang 2011), and plants (Donoghue et al 2011).…”
Section: Evidence For De Novo Emergence Of Genesmentioning
confidence: 99%